Effects of Forest Regeneration on Crickets: Evaluating Environmental Drivers in a 300-Year Chronosequence - Neucir Szinwelski; Cassiano S. Rosa; José H. Schoereder; Carina M. Mews; Carlos F. Sperber (International Journal of Zoology, 2012)
We evaluated the relation of cricket species richness and composition with forest regeneration time, evaluating canopy and litter depth as environmental drivers. Effects of forest patch area, nearest distance to the 300-year patch, cricket abundance, sampling sufficiency, and nestedness were also evaluated. We collected 1174 individuals (five families, 19 species). Species richness increased asymptotically with regeneration time and linearly with canopy cover and litter depth. Canopy cover increased linearly, while litter depth increased asymptotically. Richness was not affected by patch area and nearest distance to the 300-year patch. Richness increased with cricket abundance, and this explanation could not be distinguished from regeneration time, evidencing collinearity of these two explanatory variables. Rarefaction curve slopes increased with regeneration time. Species composition differed among patches, with no nested pattern. We suggest that regeneration and consequent increases in canopy and litter promote recovery of cricket biodiversity, abundance, and changes in species composition. We conclude that the recovery of cricket diversity involves an increase along the spatial scale of complementarity, together with a change in species composition.